The Role of Character Education in Overcoming the Moral and Social Ethical Crisis in Students - Aini, Syarifah; JS, Nur Alfiah; Ahmad, M. Ridwan Said (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The problem of moral crisis and social ethics among students is very important to pay attention to. It is important to have learning that is able to overcome this, this is certainly in line with the implementation of character education for students or learners, because freedom of access to the outside world and socializing and poor environmental conditions affect the formation of students' morals and social ethics. This study aims to identify the role of character education in overcoming the moral and ethical crisis in students. This study uses a qualitative research method using a descriptive approach. Data collection techniques in this study use observation, interview and documentation techniques as well as literature reviews. The results of the study found that character education has a very important role in overcoming or overcoming the moral and social ethical crisis in students. In this case, where character education with various values and norms such as honesty, discipline, justice, compassion and responsibility. Character education in terms of social ethics teaches a life of tolerance, mutual respect and respect for others regardless of the differences in religion or culture that are adhered to by the people around them.